Antibacterial and antifungal activities herbácia Zingiber Officinale in dentistry: a literature review (Research, Society and Development, 2020)
The pathogenic dental biofilm formed by species presents itself as a serious problem, since it contributes to the development of oral and bodily diseases. In this sense, Dentistry stands out for expanding knowledge about the oral ecosystem and performing procedures aimed at reducing its pathogenicity and improving oral health. Thus, technological advances and indiscriminate application of antibiotics have made bacterial strains resistant, with a great search for safer, more natural and effective methods. Therefore, the use of plants for healthy treatments is an area of great study in Dentistry. In the present literature review, we sought to analyze the species Zingiber officinali with its antimicrobial and antibiofilm activity. For this study, materials were searched at the BIREME, CINAHL, Cochrane Library, Embase, Google Schoolar, PubMed, Science Direct, published until August 2020. The search for the articles was carried out in August 2020, of the 3,401 studies were refined in 18. The findings showed that the plant Zingiber officinale has the capacity to inhibit certain bacteria in vitro, such as Bacillus sp., Escherichia coli, Pseudomonas aeruginosa, Streptococcus mutans and fungi, like Candida albicans. Thus, studies in the area are still needed in order to prove its effectiveness in vivo, to analyze the toxicity, drug interactions and side effects of the plant.